ENGLISH TEACHERS’ COMPETENCIES ON TPACK IN THE INDEPENDENT CURRICULUM ERA - Rachmijati, Cynantia; Cahyati, Sri Supiah (NextGen Education Review Journal, 2024)
This study explores English teachers’ perspectives on TPACK in the Independent curriculum era. While the adoption of the independent education program in Indonesian secondary schools marked a transformative phase for English language learning, teachers now have the autonomy to tailor instructional materials and pedagogical strategies to students’ unique needs. This shift indicated that however, necessitates that teachers needs to possess comprehensive digital literacy. This research uses Narrative Inquiry with forty-five (45) participants through questionnaires and interviews. The data analysis indicates that a substantial proportion of teachers are proficient in integrating technology into their teaching approaches and subject-specific content (53%). They express confidence in their ability to utilize effective teaching strategies (82%), possess a deep understanding of the subject matter (71%), the majority of teachers are capable of incorporating technology into the teaching-learning process (81%), and acknowledge their combined expertise in technology, pedagogy, and content (81%). Nevertheless, certain obstacles were encountered, including limited data quotas, limited internet access, and some teachers' reluctance to adopt technology. It is crucial that teachers effectively integrate technology, pedagogy, and content knowledge to foster students' 21st-century language proficiency.